2021
DOI: 10.3389/fmars.2021.715557
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Non-linear Interactions Between Tide, Storm Surge, and River Flow in the Delaware Bay Estuary, United States

Abstract: Low-lying coastal areas in the mid-Atlantic region are prone to compound flooding resulting from the co-occurrence of river floods and coastal storm surges. To better understand the contribution of non-linear tide-surge-river interactions to compound flooding, the unstructured-grid Finite Volume Community Ocean Model was applied to simulate coastal storm surge and flooding in the Delaware Bay Estuary in the United States. The model was validated with tide gauge data in the estuary for selected hurricane events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Attending all of this, the short-waves will have a minor impact on the inundation patterns determined in this study. Regarding rivers inflow, previous studies concluded that freshwater discharges affect the propagation of the tide throughout the estuaries, increasing the distortion and reducing the amplitude and speed, which results in a raising of the mean water levels and flood hazard 47 , 48 . Therefore, the inundation extent obtained here could be higher if river flows were considered, particularly in Ria de Aveiro, Mondego and Tagus estuaries given the floodplains adjacent to the river's channels.…”
Section: Discussionmentioning
confidence: 99%
“…Attending all of this, the short-waves will have a minor impact on the inundation patterns determined in this study. Regarding rivers inflow, previous studies concluded that freshwater discharges affect the propagation of the tide throughout the estuaries, increasing the distortion and reducing the amplitude and speed, which results in a raising of the mean water levels and flood hazard 47 , 48 . Therefore, the inundation extent obtained here could be higher if river flows were considered, particularly in Ria de Aveiro, Mondego and Tagus estuaries given the floodplains adjacent to the river's channels.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-Atlantic region of the United States is exposed to frequent tropical cyclones that bring intense precipitation and storm surge (Sun et al, 2021). In this study, we define the mid-Atlantic region as Susquehanna River Basin (SRB) and Delaware River Basin (DRB) (Fig.…”
Section: Study Domainmentioning
confidence: 99%
“…7). Gauge 8545240, despite being located at the upstream reach of Delaware Bay, is dominated by semidiurnal tides even at high-flow conditions during extreme storm events (Xiao et al, 2021). A lag time of 4 h is added to the water level data at the coastal gauge to compensate for the phase lag between this NOAA tidal gauge and that at the river mouth.…”
Section: Flood Event Simulationmentioning
confidence: 99%
“…As flood hazards combine, impact in some contexts is likely to be non-linear [23], creating tension in the systems that have only recently been designed for adaptation, such as those including elements of resilience, early warning and anticipatory action. Assessing social, economic and financial direct and indirect impact of multiform flood events are crucial steps to inform fiscal and financial policies and instruments in more comprehensive and cross-sectoral ways that accurately represent the full spectrum of their potential effects [24].…”
Section: Types Of Flood and Interactionsmentioning
confidence: 99%